Amyloid-Beta (Aβ) D7H Mutation Increases Oligomeric Aβ42 and Alters Properties of Aβ-Zinc/Copper Assemblies - Chen, Wei-Ting; Hong, Chen-Jee; Lin, Ya-Tzu; Chang, Wen-Han; Huang, He-Ting; Liao, Jhih-Ying; Chang, Yu-Jen; Hsieh, Yi-Fang; Cheng, Chih-Ya; Liu, Hsiu-Chih; Chen, Yun-Ru; Cheng, Irene H. (PLOS ONE, 2012)
Amyloid precursor protein (APP) mutations associated with familial Alzheimer's disease (AD) usually lead to increases in amyloid β-protein (Aβ) levels or aggregation. Here, we identified a novel APP mutation, located within the Aβ sequence (AβD7H), in a Taiwanese family with early onset AD and explored the pathogenicity of this mutation. Cellular and biochemical analysis reveal that this mutation increased Aβ production, Aβ42/40 ratio and prolonged Aβ42 oligomer state with higher neurotoxicity. Because the D7H mutant Aβ has an additional metal ion-coordinating residue, histidine, we speculate that this mutation may promote susceptibility of Aβ to ion. When co-incubated with Zn2+ or Cu2+, AβD7H aggregated into low molecular weight oligomers. Together, the D7H mutation could contribute to AD pathology through a “double punch” effect on elevating both Aβ production and oligomerization. Although the pathogenic nature of this mutation needs further confirmation, our findings suggest that the Aβ N-terminal region potentially modulates APP processing and Aβ aggregation, and further provides a genetic indication of the importance of Zn2+ and Cu2+ in the etiology of AD.